Use of information and communication technologies by physiotherapist and physiotherapy students in Portugal - Pinto, M (2008)
PURPOSE: This study aims to determine the use of the ICT by Physiotherapist and Physiotherapy students. RELEVANCE: The European Benchmark Statement(ER-WCPT) refers that the Physiotherapist should have skills in the area of ICT, so that he/she is able to search for the required evidence to validate his/her practice, as well as managing the data and records stemming from his/her clinical practice. Therefore those skills should be developed during their basic training and used to support and deliver Lifelong Learning PARTICIPANTS: A sample of Physiotherapy students (n=982) and Physiotherapists (n=261) from a population of members of the Portuguese Association of Physiotherapists (APF). METHODS: We use a validated questionnaire subdivided into 6 dimensions (sample characterization, equipment characterization, usage characterization, attitudes and knowledge, barriers and necessities). ANALYSIS: The procedures used were essentially descriptive statistics. RESULTS: When inquired 99% of the students reported using computer in academic activities of which 42.6% as a weekly usage between 0 and 3 hours and 36.7% between 3 and 5 hours and 57.4% referred the importance of using ICT in the school context. The Physiotherapists use more frequently the computer at home (80%), followed by the workplace for 16%, when inquired 68% reported using computer on the workplace, of which 52% also have access to the internet. Regarding the main obstacles in using ICT, 51% of students and 18,7% of the Physiotherapists refer the lack of specific knowledge in this area and 18,5% refer to the lack of time to use them. As for the training needs felt by the Physiotherapists, 19% refers having lack of training in using clinical assessment software and 17,5% refer lack of training in using exercise software for producing patient information and handouts. CONCLUSIONS: Through the analysis of the results of this study it is demonstrated that although the good accessibility to the ICT by students and professionals in their institutional and home environment the use is yet scarce because of lack of time and specific knowledge to use it. IMPLICATIONS: There seems to be the need to create institutional programs and projects that promote the usage of ICT by investing in the training of students and Physiotherapists, and promoting the usage of ICT in the workplace.